Physiology of Cotton - Stewart, James McD.; Oosterhuis, Derrick M.; Heitholt, James J.; Mauney, Jackson R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Cotton production today is not to be undertaken frivolously if one expects to profit by its production. If cotton production is to be sustainable and produced profitably, it is essential to be knowledgeable about the growth and development of the cotton plant and in the adaptation of cultivars to the region as well as the technology available. In addition, those individuals involved in growing cotton should be familiar with the use of management aids to know the most profitable time to irrigate, apply plant growth regulators, herbicides, foliar fertilizers, insecticides, defoliants, etc. The chapters in this book were assembled to provide those dealing with the production of cotton with the basic knowledge of the physiology of the plant required to manage the cotton crop in a profitable manner.
The Origin and Evolution of Gossypium -- Germplasm Resources for Physiological Research and Development -- Morphological Alterations in Response to Management and Environment -- Physiological and Anatomical Factors Determining Fiber Structure and Utility -- Germination and Seedling Development -- Growth and Development of Root Systems -- Temporal Dynamics of Cotton Leaves and Canopies -- Cotton Source/Sink Relationships -- Relation of Growth and Development to Mineral Nutrition -- Cycles and Rhythms in Cotton -- Physiology of Seed and Fiber Development -- Plant Responses to Temperature Extremes -- Plant Responses to Salinity -- Plant Responses to Mineral Deficiencies and Toxicities -- Air Pollution Stress -- Responses of Cotton to CO2 Enrichment -- Inter-Plant Competition: Growth Responses to Plant Density and Row Spacing -- Cotton Host-Microbe Interactions -- Ecophysiology of Arbuscular Mycorrhizas in Cotton -- Mechanisms of Cotton Resistance to Arthropod Herbivory -- Effects of Environment on Fiber Quality -- Physiological Responses to Tillage Systems, Cover Crops, and Residue Management -- Crop Water Management to Optimize Growth and Yield -- Interpretation of Plant Mineral Status -- Foliar Fertilization of Cotton -- Use of Growth Regulators in Cotton Production -- Physiological Rationales in Plant Monitoring and Mapping -- Physiological Simulation of Cotton Growth and Yield -- Ontogeny of Cotton Seeds: Gametogenesis, Embryogenesis, Germination, and Seedling Growth -- Secondary Products -- Neutral Nonstructural Carbohydrates -- Biochemistry of the Fiber -- Cotton Regeneration -- Current Status of Cotton Molecular Biology -- Genetic Engineering Applications in Crop Improvement.
Keywords: Life sciences; Agriculture; Botany; Plant anatomy; Plant physiology; Plant breeding; Life Sciences; Plant Physiology; Agriculture; Plant Sciences; Plant Anatomy/Development.; Plant Breeding/Biotechnology.